2001
DOI: 10.1023/a:1012865200458
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Coagulase-negative staphylococci (CoNS) are commonly associated with infections of prosthetic devices mediated by adsorbed host factors on biomaterial surfaces. Complement activation is known to occur and induce unspecific inflammation around the biomaterials. Human vitronectin (Vn) and clusterin (Clu), two potent inhibitors of complement, can be bound by CoNS. With a hypothesis whether binding of Vn or Clu influences complement activation, two measurements were determined. For Vn, complement activation was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The binding of CLU to bacteria and/or bacterial components may inhibit MAC formation. The binding of CLU to the Streptococcus pyogenes virulence protein SIC [ 77 ], the dengue virus non-structural protein 1 [ 78 ] and the Pseudomonas aeruginosa protein dihydrolipoamide dehydrogenase [ 79 ] has been reported to inhibit complement activation and MAC formation, whilst the binding of CLU to Staphylococci epidermis J9P was reported to enhance complement-induced bacterial lysis [ 80 ]. CLU was also shown to co-localise with MAC in myocardial infarction [ 81 ].…”
Section: Extracellular Chaperones (Ecs) Implicated In Complement Regu...mentioning
confidence: 99%
“…The binding of CLU to bacteria and/or bacterial components may inhibit MAC formation. The binding of CLU to the Streptococcus pyogenes virulence protein SIC [ 77 ], the dengue virus non-structural protein 1 [ 78 ] and the Pseudomonas aeruginosa protein dihydrolipoamide dehydrogenase [ 79 ] has been reported to inhibit complement activation and MAC formation, whilst the binding of CLU to Staphylococci epidermis J9P was reported to enhance complement-induced bacterial lysis [ 80 ]. CLU was also shown to co-localise with MAC in myocardial infarction [ 81 ].…”
Section: Extracellular Chaperones (Ecs) Implicated In Complement Regu...mentioning
confidence: 99%
“… Previous studies have demonstrated that the introduction of heteroatoms on the benzene ring can often endow the compounds with unique properties and broaden their applications. For example, pyridine and pyrimidine with nitrogen atoms embedded in the conjugated rings have been widely used in biopharmaceuticals. , Besides, chlorophylls play essential roles in harvesting and transferring the solar energy for splitting water and generating oxygen. , At the same time, heme is responsible for transporting oxygen in the human body . Nitrogen-containing metalloporphyrins have also been synthesized for catalysis, photochemistry, and biopharmaceutical applications. Considering the great potential of heterobenzenes in practical applications, it is valuable to devote efforts to extending the investigations on heterometallabenzenes as the simultaneous presence of metal atom and heteroatom in the benzene ring could result in more intriguing properties.…”
Section: Introductionmentioning
confidence: 99%